Phase Relations in Natural and Social Sciences: A Comparative Case Study - Gopinath, M. A.; Inder Mohan, R.; Bhandar, Krishna Mani; Saifulla, Sheik (Journal of Information and Knowledge, 1983)
Studies the incidence of phase relations in the complex subjects associated with either botany or zoology psychology or economics or sociology as a basic facet in the first phase. It is found that psychology, economics and sociology have wider range of phase relations. Botany and Zoology have phase relations largely with biosciences. It is also found, that except in the case of economics, there is progressive increase in the incidence of complex subjects.